Mediating effects of study outcomes on student experience and loyalty: A comparison of home and international students - Quintal, V.; Shanka, Tekle; Chuanuwatanakul, P. (2013)
© 2013 by IGI Global. All rights reserved. This paper aims to examine whether expectations of the student experience have an impact on student loyalty that is mediated by expectations of study outcomes at their university. To achieve this, a 15-minute pen and paper survey was self-administered to a convenience sample of students at a major university in Western Australia. The total sample size was 400 students, with 200 students each drawn from the home and international student populations. Findings suggest the university's image and facilities that prepare students for career, personal and academic development were positively related to home student loyalty, while teaching and support services that prepare students for career development were positively related to both home and international students' loyalty. Since the global trend is toward a customeroriented model, universities can remain competitive by providing the 'gestalt' student experience that helps students to achieve their study outcomes and develop loyalty toward their university.